2008
DOI: 10.1055/s-2008-1076931
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures in Perinatal Medicine – pH or BE. The Thresholds of These Parameters in Term Infants

Abstract: Thresholds in UA blood for pH, pCO2, sO2 and BE(oxy.) in term-infants are: 7.000, 84 mmHg, 3.0 % and - 20 mmol/l, respectively. Delivery of an otherwise healthy baby without getting in touch with these thresholds seems to be safe both for the baby and the obstetrician. In addition, severe neonatal depression (Apgar 1 min: 0 and 1) is usually avoided (0 / 398). BE(oxy.) does not offer a higher diagnostic power when compared with actual pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
0
21
0
4
Order By: Relevance
“…12 Another study also identified a base excess lower than À20 mmol/L as being associated with adverse outcomes. 13 A more recent study suggested a threshold pH of 7.10 for adverse neurological outcomes, with the 'ideal' cord pH being between 7.26 and 7.30. However, acidemia in this study was only weakly associated with adverse outcomes at pH >7.0, as most neonates with neurological morbidity had normal cord pH values.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another study also identified a base excess lower than À20 mmol/L as being associated with adverse outcomes. 13 A more recent study suggested a threshold pH of 7.10 for adverse neurological outcomes, with the 'ideal' cord pH being between 7.26 and 7.30. However, acidemia in this study was only weakly associated with adverse outcomes at pH >7.0, as most neonates with neurological morbidity had normal cord pH values.…”
Section: Discussionmentioning
confidence: 99%
“…However, two components (body temperature and base excess) are modifiable, so a high CRIB-II score can remind caregivers to optimize these factors as early as possible; if rectified in a timely manner, the immediate and longer-term impact may be reduced. [24][25][26][27] CRIB-II is primarily an instrument for comparing populations and does not provide individual prognoses accurately enough to dictate individual decisions. Our study revealed that infants with a CRIB-II score of 13 or above had higher rates of neurodevelopmental impairment.…”
mentioning
confidence: 99%
“…Already in 1962 E.Saling [22] pointed out that actual pH should be used in foetal acid-base studies instead of pH 40 ( = BE B,act ) still not knowing in 1962 the concept of BE Ecf [2] . Moreover according to our data it is questionable if the concept of SBE (virtually excluding the infl uence of pCO 2 on BE in vivo) is still valid using larger (N > 8 000) numbers of samples of umbilical blood (UA) including critically low pH-and critically high pCO 2 -values: Especially in severe hypoxia and acidosis (N = 390 [7] ) BE Ecf (SBE) is much more infl uenced (r = 0.489) by pCO 2 than BE B (r = 0.241, P Diff . < 0.0001), both correlations being highly signifi cant (P < 0.0001).…”
Section: Apgar-scores and Cth + / Cth + Ecfmentioning
confidence: 86%
“…2) The hydrogen ion in imperceptible concentrations is a potent eff ector to liberate oxygen from the haemoglobin molecule(s) for foetal tissue oxygen supply. As mentioned before deoxygenation leads to the appearance of NH + , NH 2 + , or NH 3 + groups in the Hb-molecule whereas free titratable hydrogen ions (more or less) disappear; If severe hypoxia occurs the foetal haemoglobin molecules are soaked with hydrogen ions like a sponge fi lled with water and haemoglobin saturation becomes very low (e. g. down to 3.0 % [7] ), in the sample of the 390 acidotic neonates with still good outcome: median sO 2 = 10.1 % ; thus oxygen is de-livered to foetal tissues avoiding at least temporarily hypoxic injuries. Therefore using the new and logical nomenclature proposed by Siggaard-Andersen [3] abandoning the mentally uncomfortable term base excess and remembering again that BE B = − ctH + B in perinatal acid-base studies we need to consider always 2 components: ctH + Ecf,act.…”
Section: Apgar-scores and Cth + / Cth + Ecfmentioning
confidence: 91%
See 1 more Smart Citation